Hydrogen production potential from agricultural biomass in Punjab province of Pakistan. (15th January 2022) - Irfan, Muhammad; Razzaq, Asif; Chupradit, Supat; Javid, Muhammad; Rauf, Abdul; Aini Farooqi, Tanzeel Javaid
Abstract: Depleting resources and popping environmental concerns instigate the development of sustainable and clean energy solutions. Amongst others, Hydrogen (H2 ) is an imperious alternative due to the lowest emissions, higher calorific value, and usability. It has great relevance in Pakistan due to sequester Agricultural biomass potential that can be used as feedstock for H2 production. So, this study estimates the H2 production potential from agricultural biomass (rice, sugarcane, cotton, wheat, and maize) of Punjab, Pakistan. In doing so, simulations are performed using Aspen Plus under various conditions to derive an optimal value of H2 output. The results indicate significant heterogeneity across districts and crop residues types. Therefore, the Geographic Information System (GIS) is used to draw the spatial distribution of optimal H2 production across crops and districts. The simulated results reveal that Punjab province has the potential to produce 2619.90 × 10 3 Metric tons (MT)/year H2, and the highest potential derives from sugarcane trash (1012.77 × 10 3  MT/year), followed by maize straw (433.67 × 10 3  MT/year). The estimated H2 potential (2.62 million MT/year) can be used in industries, transportation, and urea production as a sustainable alternative in Pakistan. Graphical abstract: Image 1 Highlights: Punjab has the potential to produce 26.2 million tons/year of H2, . Estimated H2 potential could meet above 200% of the current H2 demand for urea. Estimated H2 potential shows substantial variation across districts.